Optimasi Budidaya dan Pemasaran Maggot Black Soldier Fly di Kelompok Peternak Labung Raya untuk Bahan Pakan Sumber Protein - Eli Ratni; Montesqrit Montesqrit; Virtuous Setyaka (Warta Pengabdian Andalas)
The main problem of livestock farming is still providing qualified feed at lower costs. Commercial feed prices are not suitable for traditional farming, thus increasing production costs more. The Labung Raya farmer's group understood that the provision of maggot larvae of Black Soldier Fly (BSF) could meet the protein needs of the livestock, such as poultry and catfish. The problems raised so far were that the growth of maggot produced was not maximized, such as few eggs, small larval body size, maggot coming out of the bucket, and not optimal fermentation of maggot feed. The activity began with a brainstorming event about the negative impact of the Covid-19 pandemic on the community. The implementation of the activities was continued with the method of counselling, training, and continuous mentoring. This community engagement was welcomed by the general community and the Labung Raya breeder group's partners. The practice of cultivating Maggot BSF is straightforward for anyone to do. The cultivation process only requires simple technology and low cost but requires breeding skills for optimal results. Maggot as a product is expected to be used as an alternative protein-rich animal feed ingredient in soaring prices for conventional feed, especially for poultry.